Rare diseases and oral manifestations: what pediatric dentists should know? - Olmos Villagomez, Mariné; de Souza Furtado, Taíssa Cássia; Manfrin Arnez, Maya Fernanda; Kitazono de Carvalho, Fabrício; Mussolino de Queiroz, Alexandra; Garcia de Paula-Silva, Francisco Wanderley (Journal of Oral Diagnosis, 2024)
A rare disease affects up to 65 people per 100,000 or 1.3 per 2,000 individuals. These diseases present a variety of signs and symptoms that can vary between individuals and often resemble more common conditions, complicating early diagnosis. Rare diseases are typically chronic, progressive, and fatal, severely impacting the quality of life. They may lead to the loss of autonomy in basic functions such as walking, eating, or breathing, resulting in clinical and psychosocial suffering for both patients and their families. Most rare diseases are incurable, with treatment focused on managing symptoms, preventing progression, and reducing complications. Treatment is often handled by multidisciplinary teams. Oral care depends on the patient's overall condition and should follow standardized protocols where available, tailored to the patient's specific needs. Genetic alterations are the cause of most rare diseases, with 75% diagnosed in childhood. Many of these diseases present oral manifestations, making it crucial for pediatric dentists to recognize their significance for early diagnosis, patient referral, and treatment. Given the prevalence of rare diseases and their oral implications, it is essential for healthcare professionals to be knowledgeable about their management and appropriate clinical approaches. This paper aims to review basic concepts about rare diseases and their oral manifestations.